The Limits of the City: Atmospheres of Lockdown - Young, Alison (The British journal of criminology, 2021)
Criminological engagement with urban environments has burgeoned, including investigations into the criminological sense of place and into the atmospheres of crime and justice. This article analyses cities under lockdown in the 2020 COVID-19 pandemic. Used in numerous cities, lockdowns conjoin public health initiatives and crime control to restrict the location and activities of citizens. Drawing on textual and ethnographic exploration of lockdown in Melbourne, Australia, the article examines how we make meaning in lockdown through processes of sensory and spatial interpretation. Such an approach exposes both atmospheres of control, through the criminalization of everyday activities, and numerous instances of subversion through resistance to and adaptation of the spatial and sensorial characteristics of lockdown. The article argues for the importance of the sensory as a means of conceptualizing, repopulating and redesigning future cities after lockdown ends.